Differential effects of areca nut, tobacco, and lime on oral squamous cell carcinoma progression - Verma, Tarun Prakash; Adhikari, Sonali; Kandpal, Meenakshi; Jha, Hem Chandra (Frontiers in Cancer Control and Society, 2024)
Background Consumption of tobacco and its associated products has been linked with a high incidence of oral cancer in the Indian subcontinent. The present study aims to assess the differential effects of areca nut, tobacco, and slaked lime on the pathogenesis and progression of oral cancer. Methodology Extracts of areca nut (ANE), tobacco leaf (TLE), and lime water (LWE) were prepared and characterized. Oral keratinocyte cells (BICR10) were treated with the prepared extracts alone and in combinations. Cell apoptosis, necrosis, nuclear aberrations, and transcript expression profiles were assessed to study the cancer pathogenesis. Results An increase in apoptosis and necrosis was observed in the cells treated with ANE and ANE+LWE, while a decrease in apoptosis was observed in cells treated with TLE. We also found a variation in the size of nuclei and an increase in the number of multinuclei in the cells treated with TLE and TLE+LWE. Out of 24 head and neck cancer-related genes, we found significant upregulation in seven genes in ANE, six in ANE+LWE, 13 in TLE, 20 in LWE, and 14 in TLE+LWE treated cells. On pathway enrichment analysis, there were alterations in the “pathways in cancer,” “focal adhesion,” and “amoebiasis.” Conclusion Although areca nut has been regarded as a carcinogen, its carcinogenic potential is lesser than tobacco and lime. Moreover, adjunctive use of tobacco and lime along with areca nut may be an essential factor in the onset and progression of oral cancer.